An Exploratory Design Workshop to Elicit what Feels Natural when Interacting with an Automobile's Secondary Controls. (2nd January 2018) - Ramm, Simon; Giacomin, Joseph; Malizia, Alessio; Anyasodo, Bennett
Abstract: Exploratory design workshops were conducted using five participatory methods with 10 automobile drivers in order to understand what characterizes natural-feeling interaction with automobiles' secondary, comfort, and infotainment controls. Hands-on, artefact-focused methods were selected for their potential to understand these familiar but characteristically silent and private interactions. 'Think Aloud' analyses, flexible modelling, breaching, focus groups, and 'future fictions' were conducted in an immersive automotive workshop using real automotive controls. Some sessions took place in a parked automobile. Grounded theory thematic analysis suggested a framework with 11 themes: Familiarity and predictability, Driver in full and ultimate control, Communication with reality, Weighty physical sensations, Cabin comfort and sanctuary, Uncluttered cabin architecture, Low visual demand, Low cognitive demand, Humanlike partnership, Humanlike sentience and learning, and Humanlike verbal–auditory communication. Natural-feeling interaction may be more likely perceived in an automobile, system, or individual control that exhibits as many of the 11 themes as appropriate.